UNDERSTANDING TRANSLATION UNITS AND SHIFTS (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
This article provides a comprehensive exploration of translation units and shifts as key concepts within the realm of translation studies. The article not only elucidates the importance of translation units and shifts but also highlights the challenges faced by translators and suggests effective strategies to overcome them. Through a different examination of these essential concepts, readers are encouraged to strengthen their understanding of cross-linguistic communication and value the complex dynamics at play in the translation process.